Jokowi Leadership Model as Mayor of Solo 2005-2010 - Quraisyi Quraisyi; Marjono Marjono; Bambang Soepeno (JURNAL HISTORICA, 2017)
Jokowi applied transformational leadership during his position as the mayor of Solo in 2005-2010 through revitalation in Solo both the governmental change and the society. The questions towards the problems of this research are: How is the leadership model of Jokowi as the mayor of Solo in 2005-2010?; and what factors which affect the leadership Jokowi’s model as the mayor of solo in 2005-2010?; than what moral values of the Jokowi’s leadership model as the mayor of Solo in 2005-2010?. Hence, the objectives of this research are; To analyze the Jokowi’s leadership model as the mayor of Solo in 2005-2010, in which this reseearch can be regarded as guidance or reference or directing to a new view of the ideal leadership for Indonesia. The methodology of this research is Historical Research Methodology. The time scope of this research is form 2005-2010 and the palace of this research is in Solo. The conclusion of this research are the character of transformational leadership, internal and external factor, and also as the values humanity aspect, democracy and nationalism Keywords: Jokowi, Transformational Leadership, Solo